Aulas de campo como recurso did?tico para o ensino de geografia na educa??o b?sica - Sales, Ione dos Santos (2024)
Geography presents itself as a very broad, multifaceted and multiscale science, which sometimes requires a multiplicity of methodological procedures to better understand the nature of geographic phenomena. In this context, the role of education stands out, through field classes, a stage of Environmental Studies, as a strategy within meaningful learning, as drivers of the teaching and learning process. Therefore, to minimize the difficulties encountered by Basic Education students in understanding socio-environmental themes, from a geographical perspective, in a significant way, this research was intended to promote the development of educational practices based on field class itineraries. To this end, two questionnaires were initially applied ? one with Basic Education Geography teachers from the municipality of Barreiras and the other with students from the Col?gio Estadual de Barreirinhas, to collect information about places to compose support material for Geography classes. field, as well as relevant information that should be present in the teaching material, such as location maps, duration of routes, physical and socio-environmental characteristics, among others. After applying the questionnaires, Cachoeira do Acaba Vida and the access road to Cachoeira do Redondo were defined as places to compose the Geography field class itinerary. Subsequently, field work was carried out to collect data and then the Geography Field Class Guide ? RACGEO was prepared, teaching support material for carrying out field classes that contains information on physical and socioeconomic attributes of the points chosen to make up the route of the aforementioned itinerary. It is believed that this material will serve as a starting point for planning field classes in the Cachoeira do Acaba Vida region, as it will be made available to education professionals in the municipality.